Shape matters: unsupervised exploration of IDH-wildtype glioma imaging survival predictors - Foltyn-Dumitru, Martha; Mahmutoglu, Mustafa A.; Brugnara, Gianluca; Keßler, Tobias; Sahm, Felix; Wick, Wolfgang; Heiland, Sabine; Bendszus, Martin; Vollmuth, Philipp; Schell, Marianne (European radiology, 2025)
This study examines clustering based on shape radiomic features and tumor volume to identify IDH-wildtype glioma phenotypes and assess their impact on overall survival (OS).
Veröffentlicht: 09 September 2024
Gesehen am 24.02.2025